PERBANDINGAN FENOLIK TOTAL PADA EKSTRAK BIJI BUAH WALI (BRUCEA JAVANICA L. MERR) DENGAN METODE EKSTRAKSI MASERASI DAN SONIKASI - Baiq Rizkia Dwiyana Meliandari; Wahida Hajrin (Universitas Islam Negeri Alauddin Makassar, 2022)
Wali Fruit Seed (Brucea javanica L. Merr) is one of the traditional medicines in Indonesia that has acted as an antidiabetic, antioxidant, and anti-inflammatory. Phenolic compounds play a role in acting as a drug. The amount of phenolic can be influenced by the extraction method used. The purpose of this study was to compare the total phenolic content of wali fruit seed extract with maceration and sonication extraction methods. The advantage of maceration was the simplest and most economical method, while sonication had a short extraction time. The method of this research is the extraction process by maceration and sonication. Screening of phenolic compounds with FeCl3 reagent and determination of total phenolics by the Folin-Ciocalteau method. The results obtained were the total phenolic value with the maceration method was 61,1927±0,1560 mg GAE/g extract, while the total phenolic value with the sonication method was 67,9854±0,0968 mg GAE/g extract. This value was significantly different (p<0.05) statistically. Thus, it was found that the total phenolic by the sonication method was greater than the maceration method. KEYWORDS: wali seeds, maceration, sonication, phenolic